Motivasi Mahasiswa Memilih Program Studi Pendidikan Luar Sekolah Pada Angkatan Tahun 2022 Fakultas Ilmu Pendidikan Universitas Negeri Makassar - yuliana sindi; Latang Latang; Latif Ali (UNIVERSITAS NEGERI MAKASSAR, 2024)
This research aims to knowing the Motivation of New Students to Choose the Out-of-School Education Study Program (Study in the Class of 2022) at Makassar State University. This type of research is descriptive quantitative. The population in this study were all 2022 PLS students totaling 61 people. The sample collection technique used in this study used saturated sample technique. The data collection techniques used were questionnaires and documentation. The data analysis technique used is quantitative descriptive data analysis. The results of the descriptive analysis of the motivation of new students to choose the Out-of-School Education study program (in the class of 2022) at Makassar State University Intrinsically influencing the motivation of new students to choose the Out-of-School Education Department tends to be more on (93%) according to the goal because I hope to later work as an educational motivator. Meanwhile, extrinsically tends to be more (54%) according to the world of work indicator because I want to work in the field of PLS.